Teaching in the knowledge society new skills and instruments for teachers - Cartelli, Antonio 1954-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
"This book investigates changes induced by information and communications technology in today's education system"--Provided by publisher.
Electronic reproduction.
Keywords: Educational technology; Internet in education; Distance education; Electronic books